Tanggapan Komunitas Adat Masyarakat Desa Lagili terhadap Adopsi Teknologi Pengendalian Gulma pada Tanaman Budidaya - Halim, Halim (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
The technology development right now extended to human culture, specially LaGili’s human culture. The technology existed in agriculture activity were using the chemical for fertilizer and to control the pest, plant disease, and weed with innovation and adoption the modern agriculture of technology. The research purpose to examine the impact of technology weed control on LaGili's human culture with perception method. This research consists dependent variable ie education degree, farmer’s experience and farmer’s participation in the league. The independent variable is a farmers participation to adoption technology of weed control ie farmers be present, farmer’s ability and farmer’s suggestion. The research result shows that’s 53.33 % respondent,s degree of education is base school, 33 % secondary school and high school with 13.33 % is a degree or academic. The respondent’s experience in farmer is a low middle category as 63.33 %. The respondent’s participation in informal is low as 70 % or 21 respondent were not following a farmers group. The respondent’s participation in adoption and planning to technology weed control ie using herbicide is highest as 63.33 %.